Evaluation of the Cytotoxic Effects of Thorn Extracts from Medicinal Plants on the sf21 Cell Line (Asian Journal of Pharmaceutics (AJP), 2021)
Objective: The present study was aimed to screen the cytotoxic effect of thorn extracts of seven different plants.Methodology: The methanol extract of thorn of seven different plants were investigated for cytotoxic activity onSf21 cell line using MTT (3-(4, 5-dimetylthiazol-2-yl)-2 and 5-diphenyltetrazolium bromide) assay. After exposureof the cell line at different concentrations to the plant extract (1.56–500 μg/mL), it was found that percentage of cellviability decreased in dose dependent manner. Results: The extract of Acacia ferruginea showed potential cytotoxicactivity with IC50 value of 92.15 μg/mL against Sf21 cell line. Among the studied plants Limonia aciddisima (L),Gymnosporia senegalensis (L), Acacia nilotica and Acacia catechu (L) extracts were exhibited lesser cytotoxicactivity, whereas Acacia senegal, Aegel marmelos and Acacia ferruginea were exhibited maximum cytotoxicactivity on the Sf21 cell line and these 3 plant extracts has shown potent IC50 value of 188.5 μg/mL, 307.6 μg/mL,92.15 μg/mL respectively on Sf21 cell lines when compared to control Benzonitrile drug. It is clear from the studythat Acacia ferruginea is more cytotoxic to Sf21 cell lines compared to other plant extracts. The GC–MS study ofAcacia feruginea showed that it has 37 bioactive components, of which some of the bioactive compounds are methylmannose (57.14), phenol (8.07), cyclopropane carboxylic acid, benzene-di-carboxylic acid (0.31), hydroxy gammabutyrolactone (0.38), gamma sitosterol (3.52), Hexacosanol (3.83), and stigmasterol (4.65). Conclusion: Thebioactive components found in Acacia ferruginia are cytotoxic and insecticidal to other pest. It shows that thorn notonly defends themselves against the herbivores, but the specialized bioactive presence also plays a major defensiverole. Hence, some of the bioactive can be isolated, characterized, and be used as a potential herbicides.